A gestão escolar na proposta curricular de Santa Catarina: intencionalidades e tensionamentos - Borin, Aline (2017)
This research aimed to analyze the configuration of school management in the Curricular Proposal of Santa Catarina of 1991, 1998, 2005 and 2014.This process occurred from two terms of emancipation and performativity, presenting intentionalities and tensions of school management in Santa Catarina education from the 1980s. The leading question of the discussions was: In what way is school management structured in the Curricular Proposal of Santa Catarina? We have assumed that the curricular documents drawn up by the technicians of the State Department of Education and by the teachers of the State of Santa Catarina seek to meet the educational needs in their daily lives. The relevance of answer to this questioning is to reflect on the school management process evidenced by the curricular documents for schools in Santa Catarina. Then, the development of the research brought the historical process of elaboration of these documents related to the events occurred at state and national level, which characterize the intentions and tensions of the time. The analysis was conducted using six books of the Curricular Proposals, published and updated between the period from 1991 to 2014, using the content analysis as a methodological procedure with its peculiarities. We started from the discussion of two terms to identify the actions proposed by the curricular documents in relation to school management, so we assumed that the perspective of emancipation would be the most adequate for the development of subjects in the school context. However, given the data analyzed in the Curricular Proposals, it was possible to notice that these documents accept the perspective of historical dialectical materialism and the historical-cultural approach. This thought entered in the Santa Catarina education after the period of re-democratization of the country in 1980, the decade in which the first curricular document was elaborated. The other updates of the Curricular Proposal keep this theoretical perspective, addressing curricular subjects, multidisciplinary topics, teacher training, curricular axes and integral education. The analysis covered the stressed school management as main axis, performativity and emancipation as categories and subcategories that emerged: curriculum, interdisciplinarity, Political-Pedagogical Project, Integral Education, omnilaterality and formation journey. The conclusions allow to observe that the Curricular Proposal does not emphasize specific chapter for discussions about the school management. It was found fragments in the text that characterize approximations about management, so, by raising the subcategories linked to the emancipation category, it was possible to verify that together with the discussions about democratic school management, the CP ensures the elaboration of the Political-Pedagogical Project and the curriculum through participation and interdisciplinarity, considering the course of the subjects providing integral education.